2008
DOI: 10.1086/589555
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling the Metallicity Distributions of Gamma‐Ray Burst, Damped Lyα, and Lyman Break Galaxies atz≈ 3

Abstract: We test the hypothesis that the host galaxies of long-duration gamma-ray bursts (GRBs) as well as quasar-selected damped Ly ( DLA) systems are drawn from the population of UV-selected star-forming, high-z galaxies (generally referred to as Lyman break galaxies). Specifically, we compare the metallicity distributions of the GRB and DLA populations against simple models where these galaxies are drawn randomly from the distribution of star-forming galaxies according to their star formation rate and H i cross sect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
219
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(246 citation statements)
references
References 91 publications
25
219
1
1
Order By: Relevance
“…On the other hand, emission selected galaxies will naturally be drawn mostly from the bright end. Fynbo et al (2008) show that QSO-DLAs as well as GRB host galaxies, which are referred to as GRB-DLAs when observed in absorption, are consistent with being drawn from the same population as Lyman-break galaxies (LBGs), which are UV-selected star-forming galaxies.…”
Section: Galaxy Counterparts Of Metal-rich Dlas 2739mentioning
confidence: 60%
See 2 more Smart Citations
“…On the other hand, emission selected galaxies will naturally be drawn mostly from the bright end. Fynbo et al (2008) show that QSO-DLAs as well as GRB host galaxies, which are referred to as GRB-DLAs when observed in absorption, are consistent with being drawn from the same population as Lyman-break galaxies (LBGs), which are UV-selected star-forming galaxies.…”
Section: Galaxy Counterparts Of Metal-rich Dlas 2739mentioning
confidence: 60%
“…This study reports on an ongoing observational survey with the Xshooter spectrograph on the European Southern Observatory (ESO) Very Large Telescope (VLT) with the aim to identify and study DLA counterparts by their emission lines, and also to test observationally the hypothesis in Fynbo et al (2008) that DLAs and LBGs are drawn from the same parent population. Earlier successes within this campaign are presented in Fynbo et al (2010Fynbo et al ( , 2011Fynbo et al ( , 2013, and are summarized in Section 5 together with detections of DLAassociated emission from other campaigns.…”
Section: Galaxy Counterparts Of Metal-rich Dlas 2739mentioning
confidence: 99%
See 1 more Smart Citation
“…The correlations between metallicity and other fundamental galaxy properties such as stellar mass, luminosity, and star formation rate are crucial to understanding galaxy populations at both low and high redshifts (e.g., Tremonti et al 2004;Savaglio et al 2005;Maiolino et al 2008;Mannucci et al 2010), including DLA galaxies (e.g., Ledoux et al 2006;Fynbo et al 2008;Pontzen et al 2008;Prochaska, Hennawi, & Herbert-Fort 2008;Krogager et al 2012;Møller et al 2013). Møller et al (2013) analyze the redshift evolution of the mass-metallicity relation in a sample of 110 DLAs and report a formula (Equation 6) for estimating stellar mass given metallicity and redshift.…”
Section: Mass-metallicity Relationmentioning
confidence: 99%
“…We note that the metallicity of the GRB host galaxies are also studied via absorption lines in the GRB afterglow spectra (e.g., Fynbo et al 2008;Savaglio et al 2009;Cucchiara et al 2014), and high metallicities are found in some cases (e.g., Savaglio et al 2012). However, the absorption line study would give the metallicity averaged over the line-of-sight in the host galaxy, and its relation with the metallicity in the immediate environment of a GRB is not understood well.…”
Section: Implications For Grb/cc Sn Site Studiesmentioning
confidence: 95%